Case Study of Social Women Construction SMA Level on Learning Sports Physical Education and Health (PJOK) in Southern Semarang District (Journal of Physical Education and Sports, 2018)
The study aims to: (1) Assess and describe the social construction of female high school students in South Semarang subdistrict towards learning physical education sport and health. (2) Assess and describe the implementation of high school physical education learning to a female student in South Semarang subdistrict. The research uses descriptive qualitative research design that describes the existing events holistically and systematically. The instruments used are interview guides and blank checklist. Data collection techniques used interviews, observation, and documentation. Data analysis: qualitative naturalistic that is data analysis based on the real situation (natural). Research: Includes some social construction of female high school student level in South Semarang subdistrict to PJOK learning, (1) Seven of 10 informants construct that learning PJOK is a fun learning, (2) Six of 10 informants construct that sweating is a constraint due to learning PJOK, (3) Three of the 10 informants constructed that PJOK learning was dominated by the students' sons The conclusions of this research are: (1) the social construction of female student high school level in South Semarang subdistrict toward PJOK learning arise because of dominant environment influence (2) Implementation of PJOK Learning in accordance with female students, in particular, should separate female student classes to be more integrated learning, and teacher competence on learning PJOK especially conditioning on female student should be improved.